2015
DOI: 10.5539/jmbr.v5n1p20
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Patterns in Functionally Different Cochlear Compartments of the Newborn Rat

Abstract: In an experimental model of organotypic cultures of the stria vascularis (SV), the organ of Corti (OC) and the modiolus (MOD), we compared the expression levels and injury/hypoxia induced response of 36 genes associated with the cells´ energy-producing and energy-consuming processes, using the microarray technique. A decrease of expression was observed for most of the voltage-dependent K + -and Ca ++ -channels as an effective mechanism to lower energetic demands. We identified two gene networks of transcripts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Thus, the shift to aerobic glycolysis and lactate signaling helps "jump start" Fgf-dependent activation of neural and sensory development. Gene expression data suggest that aerobic glycolysis may occur in the cochlea of chick and rat as well, 92,93 although relevant functional studies have not yet been reported.…”
Section: Fgf In the Early Otic Vesiclementioning
confidence: 99%
“…Thus, the shift to aerobic glycolysis and lactate signaling helps "jump start" Fgf-dependent activation of neural and sensory development. Gene expression data suggest that aerobic glycolysis may occur in the cochlea of chick and rat as well, 92,93 although relevant functional studies have not yet been reported.…”
Section: Fgf In the Early Otic Vesiclementioning
confidence: 99%
“…1B). Remarkably, these cell death patterns are associated with two gene coexpression clusters, a cluster around Hif-1a (hypoxia inducible factor -1alpha), the key transcription factor that regulates adaptation to hypoxia [6] , and a cluster around several cell-death-associated transcripts that include, among other genes, the ROS-associated molecules Sod3, the inflammatory chemokine Ccl20, the glutamate associated NMDA receptor-associated complex protein NMDARA1 Grina and the glutamate transporter Slc1a3 [4,7] .…”
Section: Research Articlementioning
confidence: 99%
“…Pcp4 encodes for the small brain-specific protein Purkinje cell protein 4. We assume that the early response of Gap43 [4,7] .…”
Section: Expression Of Neuronal Growth-associated Genesmentioning
confidence: 99%